PENGGUNAAN MODEL TEAMS GAMES TOURNAMENT (TGT) DENGAN IRINGAN MUSIK KLASIK DALAM MENINGKATKAN PEMBELAJARAN IPA UNTUK SISWA KELAS V SD - Sudaryani, Nining; Suryandari, Kartika Chrysti; Salimi, Moh (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Application of Teams Games Tournament (TGT) models in Improving Science Learning at The Fifth Grade Students. The objectives of this study are: to describe the steps of application of TGT models in Science learning, learning improvement of Science learning by implementing TGT models, and to describe problems and solutions in the application of TGT models. This research iscollaborative Classroom Action Research (CAR) conducted in three cycles, consisting of planning, implementation, observation, and reflection on each cycle. The subject of this research was 18 students. Techniques of collecting data were observation, anecdotal record, and test. The conclusion of this research is the application of TGT models carried out with the right steps can improve Science learning outcomes at the fifth grade students of SDN 1 Sidomukti in the academic year of  2014/2015.Keywords: TGT models, classic music, Science Abstrak: Penggunaan Model Teams Games Tournament (TGT) dengan Iringan Musik Klasik dalam Meningkatkan Pembelajaran IPA untuk Siswa Kelas V SD .Tujuan penelitian ini adalah: untuk mendeskripsikan penggunaan model Teams Games Tournament (TGT) dengan iringan musik klasik dalam meningkatkan pembelajaran IPA tentang pesawat sederhana, meningkatkan pembelajaran IPA tentang pesawat sederhana. Penelitian Tindakan Kelas (PTK) kolaboratif ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Subyek pada penelitian ini berjumlah 18 siswa. Teknik pengumpulan data berupa observasi, anecdotal record, dan tes. Simpulan penelitian ini adalah penggunaan modelTeams Games Tournament (TGT) dengan iringan musik klasik dapat meningkatkan pembelajaran IPA tentang pesawat sederhana siswa kelas V SD Negeri 1 Sidomukti Tahun Ajaran 2014/2015.Kata Kunci : Model Teams Games Tournament (TGT), musik klasik, IPA